Network toxicological and molecular docking in investigating the mechanisms of toxicity of agricultural chemical pyraclostrobin - Shen-sui Li; Xu-dong Tian; Ju-kun Song; Ya-dong Wu; Wei-li Wang; Zheng-long Tang; Jin-bo Wang (Ecotoxicology and Environmental Safety)
The safety of agricultural products is significant to human health. Pyraclostrobin (PYR), a common methoxycarbonyl fungicide, is a crucial role in the prevention of fungal infections during the transport and storage of agricultural products, including vegetables and fruits. Using a multi-analytical approach, integrating toxicological database mining, protein-protein interaction (PPI) network analysis, and molecular docking, this study aimed to elucidate the molecular mechanisms underlying the toxicity of PYR. A total of 162 and 129 targets were identified for cancer and kidney injury, respectively, with PPI analysis pinpointing five vital targets per condition. Functional enrichment through Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genome (KEGG) pathway annotations revealed significant associations with pathways related to prostate cancer and renal impairment pathways. Molecular docking confirmed PYR's binding affinity to these targets, indicating its potential role in disease pathogenesis. Our findings underscore the imperative for stringent safety assessments of PYR, particularly concerning the risks posed by chronic exposure, and emphasize the urgency for further research to inform public health and environmental policies.